2017
DOI: 10.18203/2394-6040.ijcmph20173847
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on tobacco and alcohol abuse among medical college students

Abstract: Background: Alcohol and tobacco consumption is now considered a serious public health problem. Together, both alcohol and tobacco abuse can cause substantial health related morbidity and mortality. This study was done to assess the patter of tobacco and alcohol abuse among medical college students of Lucknow district, Uttar Pradesh, India. The objective of the study was to assess the pattern of tobacco and alcohol abuse among medical college students of Lucknow district.Methods: A questionnaire based cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…In present study the prevalence of substance use was found significantly high among males (61.62%) which was similar to the study done by Singh et al (61.29%) but much higher than that of Padhy et al where prevalence was 37.22%. 3,14 The prevalence among females (29.41%) was similar to the study of Kumari, Nath (28.8%) but significantly higher than Singh et al, (8.24%) and also Padhy et al at 7.22%. 15 This study found that major reason for substance abuse was peer pressure (93.2%) followed by special occasion (84.74%), stress (38.98%) and curiosity (16.94%) this was considerably different than the study by Singh, which found stress (43%), followed by the curiosity of alcohol and tobacco (41.5%) as the major reasons behind taking up substance abuse.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In present study the prevalence of substance use was found significantly high among males (61.62%) which was similar to the study done by Singh et al (61.29%) but much higher than that of Padhy et al where prevalence was 37.22%. 3,14 The prevalence among females (29.41%) was similar to the study of Kumari, Nath (28.8%) but significantly higher than Singh et al, (8.24%) and also Padhy et al at 7.22%. 15 This study found that major reason for substance abuse was peer pressure (93.2%) followed by special occasion (84.74%), stress (38.98%) and curiosity (16.94%) this was considerably different than the study by Singh, which found stress (43%), followed by the curiosity of alcohol and tobacco (41.5%) as the major reasons behind taking up substance abuse.…”
Section: Discussionsupporting
confidence: 82%
“…2 Deaths due to tobacco is said to rise from 1.4% in 1990 to 13.3% by 2020. 3 Substance abuse had been proven to cause various Non-communicable disease (WHO, 2018). 5.4% of the global burden of disease is contributed by Alcohol and illicit drug use.…”
Section: Introductionmentioning
confidence: 99%
“…• Though people recognize the deleterious effects of tobacco on health, very few individuals try or completely quit consuming tobacco. [35][36][37][38][39][40]43…”
Section: Tobacco Consumptionmentioning
confidence: 99%
“…The prevalence of tobacco use in adolescents reported in this study was relatively lower than those reported from other Indian States. 10 Mahanta Beauty et al…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that alcohol and tobacco are major substances being abused by young medical graduates, in spite of universal knowledge that they are source of major non communicable diseases. 10 Although these studies discuss about the adolescent's knowledge and practice of on tobacco and alcohol consumption, however, it is pertinent to understand the knowledge and practice of tobacco and alcohol among adolescent living in slums. As the country is progressing in economic front, more and more slum dwellers especially adolescents are getting into tobacco and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%